Necrolytic Migratory Erythema in a Cat with Glucagonoma Syndrome - Sahinduran, Sima; Ozmen, Ozlem (Acta Scientiae Veterinariae, 2017)
Background: Glucagonomas are very rare neuroendocrine tumors of pancreatic endocrine islets alpha cells and they produced excessive amount of glucagon hormone. Necrolytic migratory erythema (NME) is a rare dermatosis that characterized by erosive, ulcerative and crusted lesions in different sites of the skin and the common cause of this situation related to glucagon secreted tumors. NME can occur commonly in man but some rare and recent reports available the occurrence of this situation in pet animals especially dogs. Both gross and histological findings in both human and animals are similar. This paper reports a NME case with glucagonoma and diabetes mellitus (DM) by clinical, histopathological and immunohistochemical examinations. Case: A 12-year-old, cat presented with complaints of skin lesions in neck region, hyperglycemia, weight loss and history of anorexia during the 2 months. Biochemical analysis results revealed high glucose, aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP) and creatinine levels but decreased blood urea nitrogen (BUN), total protein and potassium levels. After 2 weeks of anti-diabetic drug treatment, the blood glucose level became normal and skin lesions ameliorated but anorexia and weight loss continued. The cat exhibited general weakness and pain in abdominal area. Although the clinical sings ameliorated and skin lesions and serum biochemical findings returned the relatively normal levels compared the admission, the cat died after 2 weeks of treatment and necropsy performed. At necropsy, marked cachexia, loss of skin elasticity and decreased skin thickness were observed. During the examination of abdominal cavity of the cat, there was a mass 0.5x0.5 cm in diameter, hard and grayish color was diagnosed at the pancreas. In addition, numerous whitish foci were also present the pancreatic tissue. Additionally, enlargement and paleness were noticed at the liver. Hemorrhages were observed at the liver, stomach and gut. Histopathologically pancreatic mass composed of polygonal neoplastic cells supported by thin, fibrovascular stroma characteristic for neuroendocrine tumor. But type of the cells undistinguished by histopathology for that reason immunohistochemistry performed for to evaluated insulin and glucagon secreting cells. Immunohistochemical examination revealed that only small number of insulin secreting but numerous glucagon secreting cells in the tumoral tissue and the tumor diagnosed as glucagonoma. Marked decrease were also noticed in insulin secretin cells in pancreas and together with high serum glucose levels diabetes mellitus (DM) also diagnosed to the cat. Histopathological examination of the skin revealed that decreased skin thickness, alopecia, slight inflammatory reaction and necrosis of the spinous layer. Discussion: Glucagonomas are rare tumors of pancreas even in human, and the incidence of this tumor is very rare in cat. They are usually silent tumors and they generally caused by paraneoplastic phenomena than primary clinical symptoms. The most prominent features of the “glucagonoma syndrome” are NME and DM. In human NME is commonly diagnosed in patient with glucagonoma syndrome. Very rare NME reports available in cats and dogs. The present cat had obvious clinical symptoms and typical skin lesions for NME. This report includes the very characteristic case of NME in a cat due to glucagonoma and DM, closely resembling the glucagonoma syndrome occurred in humans. Possible cause of the liver damage was also related the DM characterized high serum glucose level. We thought that liver lesions were also supported the occurrence of characteristic skin lesions.